Al-Farabi and Aristotelian syllogistics : Greek theory and Islamic practice - Lameer, Joep. (Leiden ; New York : E.J. Brill, 1994)
Al-Farabi and Aristotelian Syllogistics deals with an important chapter in the history of Aristotelian logic in early medieval Islam and offers a unique and comprehensive analysis of the writings of the outstanding Muslim philosopher Abu Nasr al-Farabi (d. 950/51).
The first part focuses on a wide range of subjects relating to syllogistic theory proper; the second part deals with its application in the context of Islamic law and theology, and concludes with an in-depth analysis of the way in which Aristotelian logic came to be integrated into Muslim political thought.
The sections on syllogistic theory proper are especially important for those interested in the theory of Arabic logic; the remaining sections are required reading for historians of Islamic law, theology, and Islamic political philosophy.
2. The qiyas fiqhi and the Prior Analytics II.23. 3. The qiyas fiqhi and assertoric syllogistics. 4. The qiyas fiqhi: al-Farabi's fourfold classification -- IX. Religion, Philosophy, and Logic. 2. The Perfect State. 3. The Political Regime. 4. The Attainment of Happiness. 5. The Book of Letters -- Index of Primary Sources -- Index of Arabic Manuscripts.
Revision of thesis (Ph. D.)--University of Leiden, 1992.
Includes bibliographical references and indexes.
Keywords: Farabi; Aristotle -- Influence; Philosophy, Arab -- Influence; Syllogism